Analysis of Judges' Decisions in Sharia Economic Disputes in Religious Courts (Case Study of Murabahah Agreement Cancellation Lawsuit) - Fajarina, Mentari (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study aims to analyze the pattern of judges' considerations in resolving Islamic economic disputes, particularly those related to lawsuits regarding the annulment of murabahah contracts in Religious Courts. The rapid growth of the Islamic economy in Indonesia has encouraged the use of murabahah contracts as a primary financing instrument, but at the same time, various legal enforcements have emerged due to violations of conditions, defaults, and non-compliance with contract implementation. The variation in judges' considerations in resolving these disputes raises questions about the consistency and quality of decisions, both in terms of the application of Islamic principles and civil law aspects. This study uses a juridical-normative method and a case study approach. Primary data were obtained from an analysis of judges' decisions on ten cases of lawsuits regarding the annulment of murabahah contracts in Religious Courts across Indonesia. Data collection was conducted through a study of court decision documents, literature related to the Compilation of Islamic Economic Law (KHES), and relevant laws and regulations. Secondary data were obtained through interviews with legal practitioners and Islamic economic experts to strengthen the analysis. This study analyzes judges' decisions in resolving Islamic economic disputes, particularly lawsuits regarding the annulment of murabahah contracts in Religious Courts. The development of the Islamic economy in Indonesia has encouraged the widespread use of murabahah contracts as a financing instrument, but has also given rise to various legal enforcement actions due to violations of conditions, defaults, or non-compliance with contract implementation. Religious Courts play a crucial role in resolving these disputes, with absolute authority based on laws and regulations and the Compilation of Islamic Economic Law (KHES). However, in practice, judges' decisions often exhibit variations in legal reasoning, both in the application of Islamic principles and civil law, raising questions about the consistency and quality of decisions. This study aims to provide a comprehensive overview of the patterns of judges' reasoning, the obstacles encountered, and recommendations for improving the quality of decisions in accordance with Islamic economic principles. Through case studies of ten decisions by Religious Courts in various regions, this research is expected to enrich the academic literature and provide practical contributions to the development of a fairer and more legally certain Islamic economic settlement system in Indonesia.